A method for determining the single ion distribution coefficient of polyamide separation membrane
Through the quartz crystal microbalance and the modified Daonan effect combined with the Sauerbrey relationship, the problem of difficult measurement of single ion distribution coefficient in the polyamide separation membrane is solved, and the precise measurement of single ions is achieved, which improves the efficiency and feasibility of thin film separation technology is improved. sex.
Patent Information
- Application Number
- CN202411094994.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The prior art is difficult to measure the transport properties of individual ions in polyamide separation membranes, especially because the presence of ion pairs affects the behavior of individual ions, and the mechanism by which salt ions pass through membrane pores remains a very debated issue.
The quartz crystal microbalance combined with the modified Donan effect was used to compare the vibration frequency changes of uncoated and coated polyamide films, and combine the Sauerbrey relationship to calculate the partition coefficient of a single ion to achieve accurate measurement of the partition coefficient of a single ion.
It provides a high sensitivity, wide applicability and easy-to-operate method, which can accurately measure the distribution coefficient of single ions in the membrane, deepens the understanding of ion transfer during film separation, thereby improving the efficiency and feasibility of film separation technology.
Smart Images

Figure CN118641403B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of membrane technology, in particular to a method for measuring the single ion distribution coefficient of a polyamide separation membrane. Background Art
[0002] Reverse osmosis (RO) technology has become the dominant technology for desalination and water purification due to its high energy efficiency and excellent product water quality. In the RO process, hydraulic pressure acts on the brine feed stream to drive water molecules through a semipermeable membrane while retaining salt ions. Currently, the most advanced RO membrane is a thin film separation membrane (TFC), which consists of a non-selective porous polysulfone support layer and an aromatic polyamide (PA) active layer. This thin (several hundred nanometers), highly cross-linked active layer is formed by interfacial polymerization of metaphenylenediamine (MPD) and trimethyl chloride (TMC).
[0003] Within the framework of solution diffusion theory, the permeation process of solutes through the active layer can be decomposed into three steps: distribution of solutes into the active layer, diffusion through the active layer, and redistribution out of the active layer. The permeability of the active layer material to the solute (P S , m 2 ·s -1 ) is the solute partition coefficient between water and the active layer (K S , unitless) and the solute diffusion coefficient in the active layer (D S , m 2 ·s -1 ) product. Therefore, quantizing K S and D S It is essential to understand the mechanism of pollutant permeation through RO membranes from a fundamental perspective and facilitates the construction of predictive transport models. In addition, the ability to quantify K S and D S It will also facilitate the development of improved active layer materials for specific applications, as this will enable the identification of transport properties (i.e., K) that must be modified in the active layer to improve performance. S , D S or both).
[0004] Through various analytical techniques, including quartz crystal microbalance (QCM), electrochemical impedance spectroscopy, and Rutherford backscattering spectroscopy, researchers have made significant progress in quantifying the partitioning of salts into the PA layer of TFC membranes. However, it is difficult to measure the transport properties of individual ions in current studies because the presence of ion pairs may affect the behavior of individual ions, thereby affecting the partitioning of ions on the membrane surface and mass transfer within the membrane. Therefore, the mechanism of salt ion passage through membrane pores remains a hotly debated issue. Summary of the invention
[0005] To solve the above technical problems, the present invention provides a method for determining the single ion distribution coefficient of a polyamide separation membrane. The method has the characteristics of high sensitivity, wide applicability and simple operation, and can accurately measure the distribution coefficient of a single ion in the membrane. This innovative method provides a new strategy and tool for in-depth understanding of the mass transfer behavior of single ions in polyamide membranes.
[0006] The present invention further describes the distribution of anions and cations on the membrane surface by combining QCM with the modified Donnan effect, so that the distribution coefficients of anions and cations can be determined separately. This method provides a new strategy and method for clarifying the mass transfer behavior of ions in polyamide membranes. This research is expected to deepen the understanding of ion transfer in the membrane separation process, thereby further improving the efficiency and feasibility of membrane separation technology.
[0007] The object of the present invention is to provide a method for measuring the single ion distribution coefficient of a polyamide separation membrane, comprising the following steps:
[0008] (1) Place the QCM gold silicon chip into the flow module of the quartz crystal microbalance, introduce deionized water, and after balancing, record the chip vibration frequency f1; then introduce salt solution, and after balancing, record the chip vibration frequency f2, where f1 is the frequency value of pure water without polyamide membrane coating, and f2 is the frequency value of salt without polyamide membrane coating;
[0009] (2) The non-woven fabric in the polyamide separation membrane is peeled off and then placed in an organic solvent to obtain a polyamide membrane without the support layer, which is taken out and bonded to the gold silicon wafer in step (1) and dried; the dried gold silicon wafer bonded with the polyamide membrane is loaded into a quartz crystal microbalance flow module, deionized water is passed through, and after balancing, the chip vibration frequency f3 is recorded; then a salt solution is passed through, and after balancing, the chip vibration frequency f is recorded 4, f3 is the frequency value of pure water coating the polyamide membrane, and f4 is the frequency value of the salt coating the polyamide membrane;
[0010] (3) Calculate the mass change m of salt distribution on the polyamide membrane using the Sauerbrey relationship salt , the Sauerbrey relationship is: ;
[0011] Where Δf is obtained by subtracting the frequency change (f2-f1) recorded by the sensor not coated with polyamide from the frequency change (f4-f3) recorded by the QCM with the sensor coated with polyamide. The difference between f2-f1 is the frequency difference of the gold silicon wafer not coated with polyamide film (frequency change caused by mass change), and the difference between f4-f3 is the frequency difference of the gold silicon wafer coated with polyamide film (frequency change caused by mass change). n is the frequency. C is the crystal constant of the gold silicon wafer. Generally, when n is 5 MHz gold silicon wafer, the specific value of C is 17.7 ng / (Hz•cm2 );
[0012] (4) Calculate the salt concentration c on the surface of the polyamide membrane by the change in the mass of the polyamide membrane s,p ,
[0013] ,
[0014] Where, δ is the thickness of the polyamide film; c s,v is the salt concentration in the polyamide membrane pores; f v is the porosity of the polyamide membrane; MW v and MW p are the molecular weight of the salt in the voids of the polyamide membrane, MW p is the molecular weight of the salt in the polyamide membrane; δ is in the approximate range of 100-150 nm and is a property of the polyamide membrane itself; c s,v It is generally considered to be the concentration of the salt solution itself; f v is the porosity of the polyamide membrane; MW v and MW p is the property of the salt itself, where MW p Affected by membrane pore size;
[0015] (5) Total ion distribution coefficient K tot , cation distribution coefficient K ct and anion partition coefficient K co , respectively calculated by the following formulas:
[0016] ,
[0017] ,
[0018] ;
[0019] Among them, z + is the valence state of the cation; z - is the valence state of the anion; c s,b is the concentration of salt solution;
[0020] The non-Donnan distribution coefficient (Φ) is obtained under strong acid conditions (pH 1-5) and high salt concentration (concentration 800-2000mmol / L) solution concentration conditions. The reason for choosing high salt concentration is that under high salt concentration and strong acid conditions, the charge density of the active layer is relatively low, which effectively shields the electrostatic effect of the polyamide film (making the Donnan potential close to 0). Therefore, the Φ value was measured here at pH 4.5, 1200 mM conditions,
[0021] Right now, ;
[0022] Daonan potential (Δφ D ) is calculated by the following formula:
[0023] .
[0024] In some embodiments of the present invention, in step (1), the deionized water equilibration time is 2 to 48 hours; and the salt equilibration time is 2 to 24 hours.
[0025] In some embodiments of the present invention, in step (1), the frequency n is any value of 3, 5, 7, 9, and 11.
[0026] In some embodiments of the present invention, in step (1), the flow rate of the peristaltic pump configured for the quartz crystal microbalance is 20-200 μL / min; and the temperature of the quartz crystal microbalance is set to 20°C-65°C.
[0027] In some embodiments of the present invention, in step (1), the pH of the salt solution is 3-11.
[0028] In some embodiments of the present invention, in step (1), the concentration of the salt solution is 10-2000 mmol / L.
[0029] In some embodiments of the present invention, in step (2), the cation of the salt in the salt solution is one of cesium, rubidium, potassium, sodium, lithium, calcium, magnesium, strontium, and barium ions.
[0030] In some embodiments of the present invention, in step (2), the anion of the salt in the salt solution is one of fluoride, chlorine, bromine, iodine, sulfate, nitrate, phosphate, carbonate, and perchlorate.
[0031] In some embodiments of the present invention, the organic solvent in step (2) is one or more of dimethylacetamide, N,N-dimethylformamide or chloroform; and the drying time is 12 to 48 hours.
[0032] In some embodiments of the present invention, the polyamide separation membrane is a nanofiltration membrane, a reverse osmosis membrane or a homemade membrane.
[0033] The above technical solution of the present invention has the following advantages compared with the prior art:
[0034] The present invention uses a quartz crystal microbalance-based technology to quantitatively characterize the single ion distribution coefficient of a polyamide separation membrane. By comparing the vibration frequency records of a quartz crystal not coated with a polyamide layer and a quartz crystal coated with a polyamide separation layer, the distribution coefficient of salt on the polyamide separation layer is accurately quantified. Combined with the modified Donan effect, the present invention further realizes the quantitative and accurate analysis of the single ion distribution coefficient. This method is simple to operate, real-time and intuitive, and can be widely used in thin-layer composite reverse osmosis membranes and nanofiltration membranes, providing an important analytical tool for solving the bottleneck problem of the mutual restriction between the permeation flux and the salt rejection rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0036] Figure 1 This is the variation curve of sodium sulfate measured on the gold silicon wafer not coated with polyamide film in Example 1.
[0037] Figure 2 This is the variation curve of sodium sulfate measured on the gold silicon wafer coated with a polyamide film in Example 1.
[0038] Figure 3 It is the distribution coefficient of the polyamide active layer of Example 3 to different concentrations of lithium ions and chloride ions. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0040] Embodiment 1:
[0041] This embodiment provides a method for determining the sodium ion and sulfate ion distribution coefficient of a polyamide separation membrane, comprising the following steps:
[0042] (1) Place a clean and dry QCM gold silicon wafer into a quartz crystal microbalance flow module (the temperature of the quartz crystal microbalance is set to 20°C, and the flow rate of the configured peristaltic pump is set to 30 μL / min), pass deionized water, and after balancing for 12 hours, record the vibration frequency f1 (n = 5, f1 = 24694763.45 Hz), then pass 50 mmol / L Na2SO4 solution, and after balancing for 11 hours, record the vibration frequency f2 (n = 5, f1 = 24694723.36 Hz) (see Figure 1 );
[0043] (2) The commercial NF90 polyamide separation membrane was soaked in 25% v / v ethanol for 30 min and then washed three times with ultrapure water. The washed polyamide separation membrane was peeled off from the non-woven fabric and placed in the organic solvent dimethylacetamide until the support layer was completely dissolved. The polyamide membrane (membrane side facing up) after the non-woven fabric and support layer were peeled off was fished out and attached to the gold silicon wafer obtained in step (1), and dried in a fume hood for 12 hours. The dried gold silicon wafer was loaded into the quartz crystal microbalance flow module, deionized water was passed through, and after balancing for 15 hours, the vibration frequency f3 (n = 5, f3 = 24687718.75 Hz) was recorded, and then 50 mmol / LNa2SO4 solution was passed through. After balancing for 10 hours, the vibration frequency f4 (n = 5, f4 = 24687647.22 Hz) was recorded (see Figure 2 ).
[0044] (3) The mass change m of the polyamide film on the gold chip is calculated using the following Sauerbrey relationship: salt The mass change of sodium sulfate distributed to the polyamide membrane was further calculated by subtracting the frequency change (f2-f1) detected by the sensor not coated with the NF90 polyamide active layer from the difference (f4-f3) of the frequency recorded by the QCM of the sensor coated with the NF90 polyamide membrane;
[0045]
[0046] Where n is 5 and C is the crystal constant of the gold-silicon wafer (17.7 ng / (Hz•cm for a 5 MHz QCM). 2 )).
[0047] The calculated mass change of sodium sulfate on the polyamide membrane is 103.72 ng / cm 2 .
[0048] (4) Calculate the sodium sulfate concentration on the membrane surface by the change in the mass of the polyamide membrane:
[0049]
[0050] Where δ is the thickness of the polyamide film (assumed to be 120 nm); c s,v is the sodium sulfate concentration in the polyamide membrane pores (50mmol / L); f v is the porosity of the polyamide membrane, which is 0.3 according to literature research; MW v and MW p are the molecular weight of sodium sulfate in the voids of the polyamide membrane and the molecular weight of sodium sulfate in the polyamide membrane (142.04 g / mol and 440.84 g / mol, the hydration number of sodium sulfate is 16.6), respectively.
[0051] The concentration of sodium sulfate on the membrane surface (c s,p ) is 0.02 mol / L.
[0052] (5) The total ion distribution coefficient of sodium sulfate is calculated by the following formula:
[0053]
[0054] Among them, c s,b 50 mmol / L;
[0055] The total ion distribution coefficient (K) of sodium sulfate on polyamide membrane was calculated. tot ) is 0.14.
[0056] (6) Under the conditions of pH = 4.5 and 1200 mmol / L sodium sulfate solution, the membrane surface is uncharged (Donnan potential is 0), then Ф (z in divalent salt) + is 1, z - is -2, c s,b 1200 mmol / L):
[0057]
[0058] The calculated Ф (equilibrium distribution coefficient of non-Donan effect) of NF90 membrane is 0.015.
[0059] (7) Daonan potential (Δφ D ) is calculated by the following formula:
[0060]
[0061] The Donan potential (Δφ D ) is -2.65.
[0062] (8) The sodium ion distribution coefficient and the sulfate ion distribution coefficient are further calculated by the following formula:
[0063]
[0064]
[0065] The distribution coefficient of sodium sulfate ions on NF90 membrane (K co ) and the sodium ion partition coefficient (K ct ) are 0.000075 and 0.21 respectively.
[0066] Embodiment 2:
[0067] This embodiment provides a method for determining the chloride ion and sodium ion distribution coefficient of a polyamide separation membrane, comprising the following steps:
[0068] (1) Place a clean and dry QCM gold silicon wafer into the quartz crystal microbalance flow module (the temperature of the quartz crystal microbalance is set to 20°C, and the flow rate of the configured peristaltic pump is set to 30 μL / min), and pass deionized water with a pH value of 4.5. After balancing for 10 hours, record the vibration frequency f1 (n = 5, f1 = 24714181.4 Hz). Then, pass 800 mmol / L NaCl solution with a pH value of 4.5. After balancing for 2 hours, record the vibration frequency f2 (n = 5, f1 = 24714068.5 Hz).
[0069] (2) After soaking the commercial RO in 25% v / v ethanol for 40 min, wash it three times with ultrapure water. The washed polyamide separation membrane is peeled off from the non-woven fabric and placed in the organic solvent N,N-dimethylformamide until the support layer is completely dissolved. The polyamide membrane (membrane side up) after peeling off the non-woven fabric and the support layer is fished out and attached to the gold silicon wafer, and dried in a fume hood for 16 hours. The dried gold silicon wafer is loaded into the quartz crystal microbalance flow module, and deionized water with a pH of 4.5 is passed through. After balancing for 13 hours, the vibration frequency f3 (n = 5, f3 = 24705417.8 Hz) is recorded, and then 800 mmol / L NaCl solution with a pH of 4.5 is passed through. After balancing for 10 hours, the vibration frequency f4 (n = 5, f4 = 24705254.7 Hz) is recorded.
[0070] (3) The mass change m of the polyamide film on the gold chip is calculated using the following Sauerbrey relationship: salt The mass change of sodium chloride distribution was further calculated by subtracting the frequency change (f4-f3) recorded by the QCM from the frequency change (f2-f2) detected by the sensor not coated with NF90 polyamide;
[0071]
[0072] Where n is 5 and C is the crystal constant of the gold-silicon wafer (17.7 ng / (Hz•cm for a 5 MHz QCM). 2 )).
[0073] The calculated mass change of sodium chloride on the polyamide membrane is 303.02 ng / cm 2 .
[0074] (4) Calculate the sodium chloride concentration on the surface of the polyamide membrane by the change in the mass of the polyamide membrane:
[0075]
[0076] Where δ is the thickness of the polyamide film (assumed to be 110 nm); cs,v is the sodium chloride concentration in the polyamide membrane voids (800mmol / L); f v is the porosity of the polyamide membrane, which is 0.3 according to literature research; MW v and MW p are the molecular weight of sodium chloride in the voids of the polyamide membrane and the molecular weight of sodium chloride in the polyamide membrane (58.44 g / mol and 279.84 g / mol, the hydration number of sodium chloride is 12.3), respectively.
[0077] Calculate the concentration of sodium chloride on the RO membrane surface (c s,p ) is 0.069 mol / L.
[0078] (5) The total ion distribution coefficient of sodium chloride is calculated by the following formula:
[0079]
[0080] Among them, c s,b 800 mmol / L;
[0081] The total ion distribution coefficient (K) of sodium chloride on the RO membrane at pH = 4.5 was calculated. tot ) is 0.043.
[0082] (6) Under the conditions of pH = 4.5 and 1200 mmol / L sodium chloride solution, the membrane surface is uncharged (Donnan potential is 0), then Ф (z in monovalent salt) + is 1, z - is -1, c s,b 1200 mmol / L):
[0083]
[0084] The calculated RO membrane Ф (equilibrium distribution coefficient of non-Donan effect) is 0.04.
[0085] (7) Daonan potential (Δφ D ) is calculated by the following formula:
[0086]
[0087] The Donan potential (Δφ D ) is -0.4.
[0088] (8) The sodium ion distribution coefficient and the chloride ion distribution coefficient are further calculated by the following formula:
[0089]
[0090]
[0091] The calculated distribution coefficients of sodium ions and chloride ions of RO membrane at pH = 4.5 are 0.039 and 0.027.
[0092] Embodiment 3:
[0093] This embodiment provides a method for determining the lithium ion and chloride ion distribution coefficient of a polyamide separation membrane, comprising the following steps:
[0094] (1) Place a clean and dry QCM gold silicon wafer into the quartz crystal microbalance flow module (the temperature of the quartz crystal microbalance is set to 25°C, and the flow rate of the configured peristaltic pump is set to 50 μL / min), pass deionized water, and after balancing for 7 hours, record the vibration frequency f1 (n = 5, f1 = 24711821.1 Hz). Then pass 100 mmol / L LiCl solution, balance for 10 hours, and record the vibration frequency f2 100 (n = 5, f2 100 = 24711755.2 Hz), then pass 200 mmol / L LiCl solution, and record the vibration frequency f2 after 13 hours of equilibrium 200 (n = 5, f2 200 = 24711736.0 Hz). Finally, 400 mmol / L LiCl solution was introduced and after 4 hours of equilibrium, the vibration frequency f2 was recorded. 400 (n = 5, f2 400 = 24711710.9 Hz);
[0095] (2) Commercial NF90 was soaked in 25% v / v ethanol for 20 min and then washed three times with ultrapure water. The washed polyamide separation membrane was peeled off from the non-woven fabric and placed in the organic solvent N,N-dimethylformamide until the support layer was completely dissolved. The polyamide membrane (membrane side facing up) after the non-woven fabric and support layer were peeled off was removed and bonded to the gold silicon wafer and dried in a fume hood for 15 hours. The dried gold silicon wafer was loaded into the quartz crystal microbalance flow module, deionized water was passed through, and after balancing for 12 hours, the vibration frequency f3 was recorded (n = 5, f3 = 24705533.5 Hz). Then, 100 mmol / L LiCl solution was passed through, and after balancing for 12 hours, the vibration frequency f4 was recorded. 100 (n = 5, f4 100 = 24705416.8 Hz), and then 200 mmol / L LiCl solution was introduced. After 13 h of equilibrium, the vibration frequency f4 was recorded. 200 (n = 5, f4 200= 24705401.3 Hz). Finally, 400mmol / L LiCl solution was introduced and after 4 hours of equilibration, the vibration frequency f4 was recorded. 400 (n = 5, f4 400 = 24705369.9 Hz);
[0096] (3) The mass change m of the polyamide film on the gold chip is calculated using the following Sauerbrey relationship: salt The frequency change (f4-f3) recorded by the QCM of the sensor coated with NF90 polyamide was subtracted from the frequency change (f2-f1) detected by the sensor not coated with NF90 polyamide, and the 100 mmol / L (Δf=(f4 100 -f3)-(f2 100 -f1))、200 mmol / L (Δf=(f4 200 -f3)-(f2 200 -f1)) and 400 mmol / L LiCl (Δf=(f4 400 -f3)-(f2 400 -f1)) mass change:
[0097]
[0098] Where n is 5 and C is the crystal constant of the gold-silicon wafer (17.7 ng / (Hz•cm for a 5 MHz QCM). 2 )).
[0099] (4) The LiCl concentration on the membrane surface was calculated based on the change in the mass of the polyamide membrane.
[0100]
[0101] Where δ is the thickness of the polyamide separation membrane (assuming 120 nm); c s,v is the lithium chloride concentration in the polyamide membrane voids (bulk solution concentration); f v is the porosity of the polyamide membrane, which is 0.3 according to literature research; MW v and MW p are the molecular weight of lithium chloride in the voids of the polyamide membrane and the molecular weight of lithium chloride in the polyamide membrane (42.39 g / mol and 238.59 g / mol, the hydration number of lithium chloride is 10.9), respectively.
[0102] (5) The total ion distribution coefficient of lithium chloride is calculated by the following formula:
[0103]
[0104] (6) Under the conditions of pH = 4.5 and 1200 mmol / L lithium chloride solution, the membrane surface is uncharged (Donnan potential is 0), then Ф (z in monovalent salt) + is 1, z - is -1, c s,b 1200 mmol / L):
[0105]
[0106] The calculated Ф (equilibrium distribution coefficient of non-Donan effect) of NF90 membrane is 0.03.
[0107] (7) Daonan potential (Δφ D ) is calculated by the following formula:
[0108]
[0109] (8) The lithium ion distribution coefficient and the chloride ion distribution coefficient are further calculated by the following formula:
[0110]
[0111]
[0112] pass Figure 3 It can be found that the distribution coefficient of lithium ions is higher than the total ion distribution coefficient and the chloride ion distribution coefficient. At the same time, as the concentration of the salt solution increases from 100 mmol / L to 400 mmol / L, the lithium ion distribution coefficient increases, while the chloride ion distribution coefficient decreases.
[0113] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for determining the single ion distribution coefficient of a polyamide separation membrane, characterized in that: The following steps are involved: (1) Place the gold silicon chip into the flow module of the quartz crystal microbalance, pass deionized water, and after balancing, record the chip vibration frequency f1; then pass salt solution, and after balancing, record the chip vibration frequency f2; (2) The non-woven fabric in the polyamide separation membrane is peeled off and then placed in an organic solvent to obtain a polyamide membrane with the support layer removed, which is taken out and laminated on the gold silicon wafer in step (1), and dried; the dried gold silicon wafer laminated with the polyamide membrane is loaded into the flow module of a quartz crystal microbalance, deionized water is passed through, and after balancing, the chip vibration frequency f3 is recorded; then a salt solution is passed through, and after balancing, the chip vibration frequency f4 is recorded; (3) Calculate the mass change m of salt distribution on the polyamide membrane using the Sauerbrey relationship salt , the Sauerbrey relationship is: ; Wherein, Δf is obtained by subtracting the frequency change Δf2 detected by the sensor not coated with polyamide from the frequency change Δf1 detected by the sensor coated with polyamide; f 1 = f 4- f 3, Δ f 2 = f 2- f 1; n is the frequency; C is the crystal constant of the gold silicon wafer; (4) Calculate the salt concentration c on the surface of the polyamide membrane by the change in the mass of the polyamide membrane s,p , , Where, δ is the thickness of the polyamide film; c s,v is the salt concentration in the polyamide membrane pores; f v is the porosity of the polyamide membrane; MW v is the molecular weight of the salt in the voids of the polyamide membrane, MW p is the molecular weight of the salt in the polyamide membrane; (5) Total ion distribution coefficient K tot , cation distribution coefficient K ct and anion partition coefficient K co , respectively calculated by the following formulas: , , ; Among them, z + is the valence state of the cation; z - is the valence state of the anion; c s,b is the concentration of salt solution; The non-Donnan distribution coefficient Φ is obtained under strong acid conditions and high salt concentration conditions. Under high salt concentration and strong acid conditions, the Donnan potential is 0; therefore, the Φ value can be measured under this condition; the pH of the strong acid condition is 1-5, and the concentration of the high salt concentration solution is 800-2000 mmol / L; Right now, ; Daonan potential Δφ D Calculated by the following formula: 。 2. The method according to claim 1, characterized in that In step (1), the deionized water equilibration time is 2 to 48 hours; the salt equilibration time is 2 to 24 hours.
3. The method according to claim 1, characterized in that In step (1), the peristaltic pump configured with the quartz crystal microbalance has a flow rate of 20 to 200 μL / min; the temperature of the quartz crystal microbalance is set to 20°C to 65°C.
4. The method according to claim 1, characterized in that: In step (1), the pH of the salt solution is 3-11.
5. The method according to claim 1, characterized in that In step (1), the concentration of the salt solution is 10-2000 mmol / L.
6. The method according to claim 1, characterized in that In step (2), the cation of the salt in the salt solution is one of cesium, rubidium, potassium, sodium, lithium, calcium, magnesium, strontium, and barium ions.
7. The method according to claim 1, characterized in that In step (2), the anion of the salt in the salt solution is one of fluoride, chlorine, bromine, iodine, sulfate, nitrate, phosphate, carbonate and perchlorate.
8. The method according to claim 1, characterized in that In step (2), the organic solvent is one or more of dimethylacetamide, N,N-dimethylformamide or chloroform; and the drying time is 12 to 48 hours.
9. The method according to claim 1, characterized in that: In step (3), the frequency n is any value among 3, 5, 7, 9, and 11.
10. The method according to claim 1, characterized in that The polyamide separation membrane is a nanofiltration membrane, a reverse osmosis membrane or a self-made membrane.
